Co-constructing practice in an online ESOL literacy methods course. Issue 5 (19th October 2016) - Peercy, Megan Madigan; DeStefano, Megan; Kidwell, Tabitha; Ramirez, Rebekah
Abstract : Understanding how online approaches to teacher education can support teacher candidates (TCs) in the central work of teaching, that of engaging in practice with learners, has become increasingly important. This study is aligned with scholarship in core practices, which asserts that opportunities to examine, engage in and reflect upon the moment-to-moment activities of teaching are crucial for TCs to learn to do them well. The study aims to contribute to the exploration of opportunities for co-constructed TC learning by examining their learning experiences in online courses. Drawing upon a sociocultural theoretical framework, the study examines synchronous interactions between three TCs and their teacher educator in the context of a fully online English for speakers of other languages literacy methods course. Specifically, we explore the following research question: what opportunities do synchronous online lesson rehearsal cycles provide for TCs' co-construction of practice?